Pengaruh Permainan Simak-Ulang-Ucap Terhadap Keterampilan Berbahasa Jawa Siswa Kelas I MI Ma'arif Tumenggungan Tahun Pelajaran 2023/2024 - Kunikmah, Arisma; Zuhdi, Ahmad; Fatiatun, Fatiatun (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2023)
The main objective of this research is to find out how to play the listen-repeat-say game and how it affects students’ mastery of Javanese language skills. This study used a quantitative approach with an experimental design of One-Group Pretest-Posttest Design. A before and after test was included in this design to measure the treatment applied. The samples in this study were 21 grade I students at MI Ma’arif Tumenggungan. The data obtained from this study prove that 1) The initial Javanese language skills of students which include speaking skills and writing skills obtained a percentage of 17% (not good enough) while listening skills and reading skills obtained a percentage of 33% (good enough). 2) The existence of the effect of the listen-repeat-say game on students’ Javanese language skills is evidenced by the results of hypothesis testing which obtained a Sig. (2-tailed) 0.000 <0.05. 3) Designing and describing the implementation of the listen-repeat-say game applied to Javanese.